2013
DOI: 10.1002/jmri.24172
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion (IVIM) MR imaging of colorectal liver metastases: Are we only looking at tumor necrosis?

Abstract: ADC variation observed in CRC metastases following systemic chemotherapy reflects a specific increase in free-molecular diffusion (D), in itself correlated to the degree of metastasis necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 33 publications
7
61
2
1
Order By: Relevance
“…Few studies report on the potential value of DW MR imaging for assessing the response of colorectal cancer metastases to chemotherapy [69,70]. Increase in ADC has been reported after treatment.…”
Section: Liver Tumorsmentioning
confidence: 98%
“…Few studies report on the potential value of DW MR imaging for assessing the response of colorectal cancer metastases to chemotherapy [69,70]. Increase in ADC has been reported after treatment.…”
Section: Liver Tumorsmentioning
confidence: 98%
“…They founded that ADC and D provided similar accuracy in assessing malignancy (AUC for ADC = 0.770; AUC for D = 0.723). Chiaradia et al [26] found that both D (r = 0.36; p = 0.035) and ADC (r = 0.4; p = 0.02) correlated with the degree of tumor necrosis, although not with viable tumor, in their study of 35 hepatic metastases from CRC. They reported that ADC and D increased within liver metastases after chemotherapy and often referred to these changes as a sign of tumor response to treatment, which corresponds well with our study results.…”
Section: Discussionmentioning
confidence: 94%
“…One of the most conspicuous advantages of IVIM is that it does not require contrast medium injection. It is believed that the IVIM parameters between malignant and benign tumors of the liver are apparently different (11)(12)(13)(14); however, these previous reports were of limited use because they included non-solid tumors, such as cysts, abscesses, or hemangiomas; hypovascular metastatic lesions; and ill-defined tumors like cholangiocarcinoma, which are hard to delineate in the analysis.…”
mentioning
confidence: 99%